Polarizing publics in Twitter through organic targeting tactics of political incivility - Kountouri, Fani; Kollias, Andreas (Frontiers in Political Science, 2023)
Research on political incivility in social media has primarily been focused on the types and frequency of impolite or uncivil language used to attack politicians. However, there is so far little evidence on the uncivil use of organic targeting tactics. We define organic targeting tactics as the ways through which users can utilize the Twitter tagging conventions (hashtags and mentions) and its “reply” feature to target specific publics and accounts other than those in their followers' list. In the discussion on the study of political incivility on Twitter we introduce organic targeting tactics as another critical element of political incivility which may involve the violation of several political civility norms or essentially alter the intensity of their violation. Based on data from Greek Twitter this paper identifies and explores how users exploited the hashtag, mention, and reply feature of Twitter to target political out- and in-group politicians and publics and wide audiences with uncivil political messages. The dataset includes 101.512 tweets containing the “Syriza_xeftiles” hashtag posted during the period between January 2015 and early June 2019, obtained from the Twitter Search API. The dataset contains only tweets from Twitter user accounts that have posted at least 30 #Syriza_xeftiles tweets during the period under study. Analyses organic targeting tactics were based on an inductive lexicon-based approach. Evidence presented in this paper indicated that Twitter users gradually learned how to weaponize the hashtag, reply, and mention features of Twitter to target more and more regularly a variety of political accounts, publics, and audiences in Greek Twitter with uncivil political narratives. The weaponization of these Twitter features often involved the combination of several political incivility dimensions, which apart from the use of insulting utterances included the use of deception through hashjacking and the discursive dimension, which in effect constituted space violations, interruptions, and discussion prevention. We argue that this practice is indicative of a qualitatively different kind of political incivility because it does not simply aspire to establish ad-hoc political publics where incivility is the norm but also to deliberately expose other political and non-political publics to uncivil political narratives. Therefore, the deliberate use of organic targeting tactics can have far wider implications on affective polarization and ultimately on democratic processes.